A preliminary study: kinetic model of drying process of pumpkins (Cucurbita moschata) in a convective hot air dryer - Hashim, Norhashila; Iroemeha, Onwude Daniel; Rahaman, Ezdalina (Elsevier, 2014)
Drying of pumpkin (Cucurbita moschata) was investigated experimentally using a hot air convective dryer. 30 samples of pumpkin with thickness of 2 mm and 4 mm were subjected to 11 hours drying at temperatures 50 °C, 60 °C and 70 °C respectively. The drying data were fitted to the Moisture Ratio (MR) models, which produced MR = aexp-kt as the model of prediction. Selection of the best model was investigated using statistical analysis of variance, carried out via SPSS 17.0. Lewis, Henderson and Pabis models gave the best prediction with R (97.1%), R2 (94.2%), SSE (0.577) and R (95.7%), R2 (91.6%), SSE (0.703) respectively.